MODEL PENINGKATAN BEHAVIORAL LOYALTY MELALUI PREFERENTIAL TREATMENT, INTERPERSONAL COMMUNICATION DAN RELATIONSHIP SATISFACTION - Ken Sudarti; Siti Nona Darmayanti (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research is to influence preferential treatment and interpersonal communication to behavioral loyalty at BRI Syariah Central Java with relationship satisfaction as intervening variable. The population used is all priority customers of BRI Syariah Semarang by 132 respondents. The analysis tool is Partial Least Square. The result of inner model test shows that preferential treatment and interpersonal communication have positive significant effect on relationship satisfaction and behavioral loyalty. Relationship satisfaction has a positive and significant effect on behavioral loyalty. Relationship satisfaction can not be an intervening variable between preferential treatment to behavioral loyalty. The result of the mediation test shows that relationship satisfaction is not able to be the intervening variable between preferential treatment to behavioral loyalty. Thus preferential treatment only affect the behavioral loyalty does not have to through relationship satisfaction. Relationship satisfaction can be an intervening variable between interpersonal communication to behavioral loyalty, giving understanding that the more effective interpersonal communication, the communication will facilitate the interaction because the information conveyed can be accepted easily, so the customer will feel satisfaction and it will certainly have an impact on customer behavior using the bank.Keywords: preferential treatment, interpersonal communication, relationship satisfaction and behavioral loyalty.